CORRELATION OF ZAKAT DISTRIBUTION WITH GINI INDEX: MAXIMIZING THE POTENTIAL OF ZAKAT FOR EQUITABLE INCOME DISTRIBUTION IN INDONESIA - Fadila, Nisa Rahma (Airlangga International Journal of Islamic Economics and Finance, 2019)
This study aims to determine the correlation of zakat distribution with the Gini index. The unequal distribution of income shown by the Gini index is an economic problem facing Indonesia today. Zakat as an instrument in the Islamic economic system can be a solution for equal distribution of income in Indonesia. The data analysis technique used is Pearson correlation analysis. The results of this analysis indicate that the distribution of zakat has a significant correlation with the Gini index.